Know Your Customer: Relationship Lending and Bank Trading - Rainer Haselmann; Christian Leuz; Sebastian Schreiber (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2021)
In this study, we analyze the trading behavior of banks with lending relationships. We combine detailed German data on banks' proprietary trading and market making with lending information from the credit register and then examine how banks trade stocks of their borrowers around important corporate events. We find that banks trade more frequently and also profitably ahead of events when they are the main lender (or relationship bank) for the borrower. Specifically, we show that relationship banks are more likely to build up positive (negative) trading positions in the two weeks before positive (negative) news events, and also that they unwind these positions shortly after the event. This trading pattern is more pronounced for unscheduled earnings events, M&A transactions, and after borrower obtain new bank loans. Our results suggest that lending relationships endow banks with important information, highlighting the potential for conflicts of interest in banking, which has been a prominent concern in the regulatory debate.
urn:nbn:de:hebis:30:3-616620
Keywords: 330